Binary decision diagram-based reliability evaluation of k-out-of-(n + k) warm standby systems subject to fault-level coverage. (October 2013) - Zhai, Qingqing; Peng, Rui; Xing, Liudong; Yang, Jun
Warm standby sparing is a fault-tolerance technique that attempts to improve system reliability while compromising the system energy consumption and recovery time. However, when the imperfect fault coverage effect (an uncovered component fault can propagate and cause the whole system to fail) is considered, the reliability of a warm standby sparing can decrease with an increasing level of the redundancy. This article studies the reliability of a warm standby sparing subject to imperfect fault coverage, in particular, fault level coverage where the coverage probability of a component depends on the number of failed components in the system. The suggested approach is combinatorial and based on a generalized binary decision diagrams technique. The complexity for the binary decision diagram construction is analyzed, and several case studies are given to illustrate the application of the approach.